2012
DOI: 10.1039/c2fo00006g
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments on polyphenol–protein interactions: effects on tea and coffee taste, antioxidant properties and the digestive system

Abstract: Tea and coffee are widely consumed beverages across the world and they are rich sources of various polyphenols. Polyphenols are responsible for the bitterness and astringency of beverages and are also well known to impart antioxidant properties which is beneficial against several oxidative stress related diseases like cancer, cardiovascular diseases, and aging. On the other hand, proteins are also known to display many important roles in several physiological activities. Polyphenols can interact with proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
197
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(204 citation statements)
references
References 108 publications
2
197
0
5
Order By: Relevance
“…The large products of interactions were formed as a result of aggregation or cross-linking as it was shown by Faergemant et al [29] and Rawel et al [30]. From the above, it could be concluded that higher temperature promoted the intensity of interactions between the proteins and polyphenols carried out at pH 6.45 [17]. HCAs inclusion in the β-CD molecule resulted in limitation of AMM increase compared with proteins heated with free HCAs.…”
Section: Molecular Mass and Proteolytic Digestion Susceptibility Of Pmentioning
confidence: 62%
See 1 more Smart Citation
“…The large products of interactions were formed as a result of aggregation or cross-linking as it was shown by Faergemant et al [29] and Rawel et al [30]. From the above, it could be concluded that higher temperature promoted the intensity of interactions between the proteins and polyphenols carried out at pH 6.45 [17]. HCAs inclusion in the β-CD molecule resulted in limitation of AMM increase compared with proteins heated with free HCAs.…”
Section: Molecular Mass and Proteolytic Digestion Susceptibility Of Pmentioning
confidence: 62%
“…Coffee bean extracts could be added to various kinds of food products, including those rich in proteins [15]. Previous studies have shown that this kind of combinations caused partial degradation of essential amino acids and reduced the susceptibility to proteolytic digestion [16,17]. Therefore, it could be more beneficial to encapsulate Abstract Polyphenol-protein interactions during food processing may cause deterioration in protein nutritional quality status.…”
Section: Introductionmentioning
confidence: 99%
“…Tannins are an abundant component of vascular plant tissue and help protect plants against bacterial and fungal infection (35). In addition, tannins are thought to be partially responsible for the astringent taste of red wines and tea (36,37). We therefore wondered if a tannin-containing drink, such as tea, would directly affect biofilms by the same isaA-dependent mechanism as tannic acid.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant properties of polyphenols make them benefi cial to health. On the other hand, polyphenols can interact with enzymatic proteins subsequently changing their molecular confi guration, which leads to reducing the catalytic activity of digestive enzymes (BANDYOPADHYAY et al, 2012). Thus, understanding of interaction between polyphenols and digestive enzymes, it is important to minimize the antinutritional effects of polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…However, tea polyphenols may reduce food digestibility by inhibiting digestive enzymes. Studies have shown that phenolic compounds from plants have a strong ability to interact with food proteins and show strong complexing abilities with enzymes (SPENCER et al, 1988;DUBEAU et al, 2010;YUKSEL et al, 2010;BANDYOPADHYAY et al, 2012). The binding interactions of tea catechins with digestive enzymes were found to denature the catalytic activity of enzymes, which reduced food digestibility (HE et al, 2006).…”
mentioning
confidence: 99%